Prospects of Levofloxacin Use in Therapy of Patients with Bronchopulmonary Diseases or Skin and Soft Tissue Pyo-Inflammatory Lesions - V. I. Sokolova; D. A. Sychev; M. B. Babarina; D. A. Zaikov (Антибиотики и Химиотерапия)
The results of the clinico-microbiological investigation of the levofloxacin efficacy in the treatment of 38 patients with respiratory infections or various pyo-inflammatory lesions are presented. The positive results were stated in 29 (76.3%) patients. No adverse reactions were observed.